Field Method for Characterization of Deciduous Wooden Shingles - Lindblad, Linda; Melin, Karl-Magnus (FormAkademisk, 2023)
In the Nordic countries, a major part of the built heritage is constructed of wood and on churches it is still common for the roofing to consist of shingles. In the 20th century, there was a paradigm shift when the heritage authorities made new standards where, for example, the variety of species used throughout history was replaced by pine with sapwood. Today, it is evident that the broken traditions have resulted in roofings with shorter life spans (Göllas & Lindblad, 2021). Further, changes in forestry during the last century made old mature pines, appropriate for shingles, a scarcity. Until last year, it was common that wood for shingles was imported from Russia and northern Finland, which is questionable from more than one perspective. In a project by the Craft Laboratory, the aim is to reclaim traditional know-how through craft research. Old built-in shingle roofs are examined, old forestry and building literature is inventoried and tradition bearers are interviewed. Several of these sources put forward oak and aspen as species well suited for long-lasting shingle roofing. The focus of the exhibition is the development of a field method in which we present features to define wood species on the weathered surfaces of shingles using sight and touch characterization. A built-in roof with both aspen and oak shingles in Tönnersjö church in Halland will serve as an example.